Multicriteria assessment of selection quality of personnel on safety management for work at the enterprises of JSC RZD - V. M. Ponomarev; I. A. Kosarev (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
In article the multicriteria method of an assessment of selection quality of personnel on safety management for work at the enterprises of JSC RZD is offered which based on the principle of selection by a complex of individual criteria. One of such approaches is based on use of a method of the main component (MC). The method of group of companies assumes transition from a large number of initial characteristics of object to a small number of the formal generalized variables - main components. At the same time the first two or three groups of companies can explain 60 - 90 % of the specified general variability. In the work for personnel appraisal in the field of occupational safety and health five tests chosen by JSC “VNIIZhT” to assess compliance of employees with the goals set by guidance for development of means and technical solutions to ensure occupational safety at JSC “Russian Railways” companies. To obtain the results a trial assessment was conducted among employees of “Occupational Safety” division to identify the most important test on the following criteria: motivation, technical intelligence, security prevention instructions and general knowledge of labor protection. The main indicator for the selected candidates is the average value of the method proposed in the article using the method of main components. The calculations are performed with the assistance of “Stadia” program. Analysis of the correlation matrix revealed that in the original sample of individuals the value of their individual indicators are correlated, so the use of MC method for building generalized index of their evaluation (instead of usual amount of individual indicators) is justified.